Proteomic Analyses of Whitefly-Begomovirus Interactions Reveal the Inhibitory Role of Tumorous Imaginal Discs in Viral Retention - Zhao, Jing; Guo, Tao; Lei, Teng; Zhu, Jia-Chen; Wang, Fang; Wang, Xiao-Wei; Liu, Shu-Sheng (Frontiers in Immunology, 2020)
In nature, plant viruses are mostly transmitted by hemipteran insects, such as aphids, leafhoppers, and whiteflies. However, the molecular mechanisms underlying the interactions between virus and insect vector are poorly known. Here, we investigate the proteomic interactions between tomato yellow leaf curl virus (TYLCV, genus Begomovirus), a plant virus and its vector whitefly (Bemisia tabaci). First, using a yeast two-hybrid system we identified 15 candidate whitefly proteins interacting with the coat protein of TYLCV. GO and KEGG pathway analysis implicated that these 15 whitefly proteins are of different biological functions/processes mainly including metabolic process, cell motility, signal transduction, and response to stimulus. We then found that the whitefly protein tumorous imaginal discs (Tid), one of the 15 whitefly proteins identified, had a stable interaction with TYLCV CP in vitro, and the DnaJ_C domain of Tid (301-499aa) may be the viral binding site. During viral retention, whitefly protein Tid was observed to accumulate at protein level, and feeding whiteﬂies with dsRNA or antibody against Tid resulted in higher quantity of TYLCV in whitefly body, suggesting the role of Tid in antiviral infection. Our data indicate that the induction of Tid following viral acquisition is likely a whitefly immune response to TYLCV infection.